The Global Kidney Exchange: Revisiting exploitation arguments. Issue 1 (28th February 2021) - Reyneke, Maryn; Borry, Pascal
Abstract: The Global Kidney Exchange (GKE) program, introduced by Rees et al . (2017), has been described as an innovative method to address the global shortage of kidneys for the purpose of transplantation. However, the concept of the GKE has evoked controversy and various international bodies have accused it of being a form of low‐ and middle‐income country (LMIC) exploitation. Using Julian Koplin's framework of exploitation, we consider three different conceptualizations of wrongful advantage taking in the unique setting formed by the GKE. The analysis contributes to a better understanding of the controversy and gives insight into how to deal with background conditions that influence the fairness of such a global social cooperation.